Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine